Preventive strategies for feeding intolerance among patients with severe traumatic brain injury: A cross-sectional survey - Yuli Fang; Yuanyuan Ma; Haiyan He; Ting Chen; Jingjing Fu; Jingci Zhu (Elsevier, 2022)
Objectives: This study aimed to investigate the application status of preventive measures for feeding intolerance in patients with severe traumatic brain injury (STBI) in China and analysis the differences and their causes. Methods: A cross-sectional survey was conducted. From December 2019 to January 2020, ICU nurses and physicians of 89 hospitals in China were surveyed by using a questionnaire on preventive strategies for feeding intolerance in patients with STBI. The questionnaire included two parts: the general information of participants (10 items) and application of preventive measures for feeding intolerance in STBI patients (18 items). Results: Totally 996 nurses and physicians completed the questionnaire. Among various methods, gastrointestinal symptoms(85.0%) and injury severity (71.4%) were mostly used to assess gastrointestinal functions and risk of feeding intolerance among STBI patients, respectively. Initiating enteral nutrition (EN) within 24-48 h (61.5%), nasogastric tubes (91.2%), 30°-45° of head-of-bed elevation (89.5%), continuous feeding by pump (72.9%), EN solution temperature of 38-40 °C (65.5%), <500 ml initial volume of EN solution (50.0%), monitoring gastric residual volume with a syringe (93.7%), and assessing gastric residual volume every 4 h (51.5%) were mostly applied for EN delivery among STBI patients. Prokinetic agents (73.3%), enema (73.6%), probiotics (79.0%), antacid agents (84.1%), and non-nutritional preparations as initial EN formula (65.6%) were commonly used for preventing feeding intolerance among STBI patients. Conclusions: The survey showed that nurses and clinicians in China have a positive attitude towards preventive strategies for feeding intolerance. However, some effective new technologies and methods have not been timely applied in clinical practice. We suggest that managers, researchers, clinicians, nurses, and other health professionals should collaborate to explore effective and standard preventive strategies for feeding intolerance among patients with STBI.